Adoption and Impact of Wheat variety HD 3086: An analysis using structural equation modeling - BHOOSHAN, NEERU; SINGH, AMARJEET; SHARMA, AKRITI (The Indian Journal of Agricultural Sciences, 2022)
Varietal development plays a crucial role in improving the overall yield of a crop and the impact assessment of a particular variety is essential to support this statement. Present study was carried out in North-Western Indo-Gangetic Plains (Punjab, Haryana and Western Uttar Pradesh) in India during 2017–18 to observe the response on the yield with the adoption of newly developed yellow rust resistant wheat variety HD 3086. The Structural Equation Model (SEM) was used to establish a relationship between the rate of adoption and factors affecting the same. Households (1000) were surveyed through random sampling for the study. Punjab was found to have the highest adoption rate amongst the 3 states followed by Haryana. This study has observed an increasing trend in coverage of farm area under HD 3086 in Punjab and Haryana. However, in Uttar Pradesh creating awareness among the seed companies and Krishi Vigyan Kendra (KVK) centres was found imperative for the multiplication of HD 3086.